Enhanced Bending Resistance and Efficiency of Flexible PSCs Derived from Self‐Healing and Passivation Double Function of a Silane Coupling Agent. Issue 26 (17th August 2022) - Lei, Yue; Li, Haimin; Liu, Xingchong; Wang, Hanyu; Ni, Yafei; Gong, Xiaoli; Zou, Wenjing; Tang, Yanling; Liu, Shuqian
Abstract: Flexible perovskite solar cells (f‐PSCs) show promising applications because of their lightweight and flexible properties. However, f‐PSCs still suffer from low efficiencies and poor stabilities. Here, vinyl tri (2‐methoxyethoxy) silane (VTMES) is introduced between perovskite and hole transport layer. The oxydic silane coupling agent effectively suppresses PbI2 formation in perovskite by forming PbO bonding, which greatly improves perovskite phase. Kelvin probe force microscopy (KPFM) results demonstrate that p ‐type doping is formed in the modified device, which effectively inhibits carrier recombination. The silane coupling agent plays double role in the devices. On one hand, it greatly improves the bending resistance of f‐PSCs due to its excellent self‐healing properties, on the other hand, it obviously suppresses defects and restrains carrier recombination of the devices by facilitating perovskite grain growth. As a result, f‐PSCs with a champion efficiency of 17.01% increased from 15.28% are achieved with high reproducibility. Meanwhile, f‐PSCs present robust bending resistance. Optimal modified devices can maintain 92% of their initial efficiency after 3000 bending cycles, while the control one can only remain 55%. This work paves a new path for f‐PSCs to improve photovoltaic properties and bending resistance by oxydic silane coupling agents. Abstract : The silane coupling agent vinyl tri (2‐methoxyethoxy) silane (VTMES) is an efficient interface modifier to improve the power conversion efficiency (PCE) and stability of flexible perovskite solar cells (F‐PSCs).